G236(P) Analysing the incidence of congenital hypothyroidism in the local area. (12th March 2018) - Tattersall, RS; Nicholls, R; Kumar, Y
Abstract : Aims: This study aims to establish the incidence of congenital hypothyroidism (CH) and the sub-type most prevalent in the local area. A secondary aim is to assess the correlation between the dosage of thyroxine replacement in dyshormonogenesis (CHD) and recovery potential. Furthermore, it will look for any link between Down syndrome and CH. Method: Data from patients diagnosed with CH over a 16 year period was analysed to find the incidence, type of CH and, if CHD, dose of leveothyroxine and outcome of a recovery test if undertaken. Whether there were any associated co-morbidities was also recorded. Results: From 55 patients, 50 originally from the local area, 47 were analysed, with full records not available for the rest. The most prevalent form was CHD with 22 cases followed by lingual thyroid in 13. The dose of levothyroxine in CHD was variable, ranging from 25 mcg to 200 mcg daily. A few patients with CHD were too young for the recovery test (8 patients) but, of the 14 patients offered the test, only 8 accepted. 6 of these 8 patients showed full recovery of thyroid function, with a lower levothyroxine dose evident in 5 cases. 2 of these patients had associated co-morbidities – Down syndrome and Deletion 1q21.1 syndrome. Overall, 4 patients with CHD had associated co-morbidities, whereas no other forms of CH had any. Conclusion: The incidence of CH in the local area is approximately 1 in 1200, much higher than the UK average of 1 in 4000. Dyshormonogenesis accounts for the greatest proportion of CH (40%) compared to established literature where it is shown to be 10%–20%. Further investigation, therefore, is required to see why CHD is more common in this area. There is insufficient information available to draw conclusions with regards to likelihood of recovery. However, the study is suggestive of recovery being more likely with a lower dose of levothyroxine, and for those patients with associated syndromes. In order to test this hypothesis, a larger study needs to be undertaken.